Online Quadace Gamestore: Selling, Renting and Trading Video Games Online - Oh, Soong Teng; Salama A. Mostafa (Applied Information Technology And Computer Science, 2022)
The Selling, Renting and Trading Video Games Online for Quadace Gamestore is a web-application which act as a platform for Quadace Gamestore to do their business online. The purpose of developing this system is to solve the problem of decreasing profit in their business during MCO. This system allows customers to purchase, rent or trade game products online. Product information will be displayed according to their category in the home page. To ensure the safety of user, they are required to register or login before they can make any payment. The user of the system will be administrator. The functional modules are login module, customers management module, product management module, ordering management module and generate report module. The software using will be Microsoft Visual Studio Code and the database used is Microsoft SQL Server Management Studio 18. Through the system, customer can make order through the system online while the administrator will deliver their game product to their doorstep. The development of this system will make the business of Quadace Gamestore better because more people may access to their shop through online website.